IDENTIFIKASI FLAVONOID DAUN TEH HIJAU (Camelia sinensis L. Kuntze) SECARA REAKSI WARNA DAN KROMATOGRAFI LAPIS TIPIS - Afriani Kusumawati (As-Syifaa Jurnal Farmasi, 2016)
Green tea plant (Camellia sinensis L. Kuntze) were examined in this study were taken from green tea products Cap Head Djenggot, from the area of Solo, Central Java. This plant thrives in the area of Green Tea plantation in the Solo area. For identification of the content of flavonoids in green tea leaves can be done Thin Layer Chromatography is accompanied by a color reaction.Spotting obtained detected with ammonia vapor is then observed with UV light UV 254 nm and 366 nm. In observation using a 254 nm UV light there is a blackish brown spots on the fraction of water-chloroform, the chloroform fraction of the spots are a light green color, and the n-butanol fraction contained a brown patches muda.Dengan using 366 nm UV rays are one dark brown spots on the fraction of water-chloroform, the chloroform fraction contained patches of light green color, and the n-butanol fraction contained a light brown spots.Based on data obtained from the reaction of color and Thin Layer Chromatography showed that the compound contained flavonoids in green tea leaves.